Выявление технологических дефектов в высоковольтной твердой изоляции электроизоляционных конструкций по характеристикам частичных разрядов - Беспрозванных, Анна Викторовна; Кессаев, Александр Геннадиевич; Мирчук, Игорь Анатолиевич; Рогинский, Александр Владимирович (Национальный технический университет "Харьковский политехнический институт", 2019)
Определены возможные значения напряжения начала частичных разрядов для модели цилиндрического воздушного зазора вблизи токопроводящей жилы силового кабеля. Показано, что при одинаковых приложенных напряжениях к высоковольтной изоляции в последнем случае активизируются воздушные включения меньшей толщины в сравнении с плоской конструкцией. На основании результатов проведенных испытаний силового кабеля на напряжение 3 кВ установлено, что грубые технологические дефекты в толще изоляции отсутствуют. Амплитуда разрядов в воздушных включениях не превышает 10 пКл при приложенном испытательном напряжении 5 кВ частоты 50 Гц. Показана эффективность выявления технологических дефектов в твердой композитной корпусной изоляции статорной об-мотки турбо- и гидрогенераторов. Установлено, что в макетах, изоляция которых выполнена лентами меньшей толщины, технологические дефекты расположены в толще изоляции. Для макета, изоляция которого выполнена лентами большей толщины, технологические дефекты в виде расслоения расположены на границе раздела проводник – композитная изоляция.

Introduction. High-voltage insulation systems always have some background level of the partial discharges, which does not have any significant effect on the life of the electrical insulation design. At the same time, partial discharges destroy high-voltage insulation, leading to a carburization zone around the defect. This is the «hidden» period of development of the defect. The development of a defect zone, sooner or later, leads to an arc breakdown of the entire insulating gap. Purpose. The substantiation of the efficiency of detection of technological defects in high-voltage solid insulation of electrical insulating structures according to the characteristics of partial discharges. Methodology.The conditions for the ocсurrence of partial discharges in the thickness of the polymer insulation are considered. The possible values of the voltage of the beginning of partial discharges are determined for a model of a cylindrical air gap near the conductor of a power cable. It is shown that with the same applied voltages to high-voltage insulation, in the latter case, air inclusions of smaller thickness are activated in comparison with a flat structure. Practical value.The efficiency of detection of technological defects in solid composite case insulation of the stator winding of turbo- and hydrogenerators is shown. Based on the comparison of the amplitude of the pulses of partial discharges of positive and negative polarity, the estimated location of the technological defects in the insulation has been established.
Identification of technological defects in high-voltage solid insulation of electrical insulation structures on the characteristics of partial discharges
Keywords: напряжение начала частичных разрядов; стекло-слюдобумажная лента; амплитуда импульсов частичных разрядов; место расположения дефекта; voltage of the start of partial discharges; glass-mica paper tape; amplitude of pulses of partial discharges; location of the defect